2012
DOI: 10.1002/ange.201203107
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydroalkynylation of Norbornadienes Promoted by Chiral Iridium Catalysts

Abstract: Alkin Ahoi: Die iridiumkatalysierte asymmetrische Hydroalkinylierung unpolarer Alkene gelang mit guten bis hervorragenden Enantioselektivitäten (siehe Schema; cod=1,5‐Cyclooctadien, DCE=1,2‐Dichlorethan). Das Katalysatorsystem ist mit funktionellen Gruppen wie NH2, OH, Br, F und SiMe3 gut kompatibel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Our group has developed the first asymmetric hydroalkynylation reaction of norbornadienes 8 promoted by a chiral catalytic system of [{Ir(cod)Cl} 2 ] and ( R )‐Synphos in DCE at 70 °C . The corresponding addition products 21 were obtained in good to high yields with good to excellent enantioselectivity (up to 97% ee ).…”
Section: Alkynylation Of Norbornadiene and Its Derivativesmentioning
confidence: 99%
“…Our group has developed the first asymmetric hydroalkynylation reaction of norbornadienes 8 promoted by a chiral catalytic system of [{Ir(cod)Cl} 2 ] and ( R )‐Synphos in DCE at 70 °C . The corresponding addition products 21 were obtained in good to high yields with good to excellent enantioselectivity (up to 97% ee ).…”
Section: Alkynylation Of Norbornadiene and Its Derivativesmentioning
confidence: 99%
“…We have established two different chiral iridium catalysts and realized the asymmetric [2+2] cycloaddition reaction [10] and the asymmetric hydroalkynylation reaction. [11] Using (S)-NMDPP as chiral ligand, we had also developed an efficient iridium catalyst for the asymmetric ring opening reaction of oxabenzonorbornadienes with phenols or naphthols. [12] Recently, we found that the complex of PdCl 2 and Xantphos could promote the ring opening reaction of oxa/azabenzonorbornadienes smoothly by employing arylacetylenes as nuleophiles.…”
mentioning
confidence: 99%
“…Recently, we found that the metal complex comprising an [IrA C H T U N G T R E N N U N G (COD)Cl] 2 precursor and the axially chiral ligand SYNPHOS ([(5,6),A C H T U N G T R E N N U N G (5',6')-bis(ethylenedioxy) biphenyl-2,2'-diyl]bis(diphenylphosphine)) is highly effective for promoting asymmetric hydroalkynylation of norbornadiene derivatives. [13] Upon changing the ligand structure to the planar chiral Xylylphanephos, the resulting catalyst system complementarily promoted the asymmetric [2+2] cycloaddition reaction between norbornadiene derivatives and terminal alkynes. [14] Herein, we report a chiral iridium catalyst system, which is generated in-situ from (S)-(+)-neomenthyldiphenylphosphine ((S)-NMDPP) and [IrA C H T U N G T R E N N U N G (COD)Cl] 2 , for ARO of oxabenzonorbornadienes with phenols or naphthols.…”
mentioning
confidence: 99%
“…Although all of the screened solvents allowed the catalytic ARO reaction to proceed, N,N-dimethylformamide (DMF) was the final choice. DMF afforded a balanced outcome in terms of the highest enantioselectivity along with good yield ( [10][11][12][13]. The complex of [IrA C H T U N G T R E N N U N G (COD)Cl] 2 with an equimolar amount of (S)-NMDPP was ineffective.…”
mentioning
confidence: 99%